Employing desirability function analysis for the multi-response optimisation of mild steel embossed plate shear connector using Taguchi technique. (December 2022) - Vijayakumar, R.; Pannirselvam, N.
Highlights: Mechanical characteristics of the shear connector with frictional interlock is studied. Optimization of the Ultimate load and relative slip are done using Desirability function analysis. Significant of the responses are studied by ANOVA. Abstract: This paper presents a novel method for studying the structural behaviour of mild steel embossed plate shear connector (MSEP) using desirability function analysis (DFA). From the test results, the ultimate load and relative slip were calculated and optimised by desirability function analysis to arrive at the optimum parameters of the shear connector compatible with a higher ultimate load and lower relative slip. The optimum levels of parameters were chosen based on the Taguchi approach of composite desirability and their significance was determined by analysis of variance. The experimental values are validated by using the finite element analysis method and the optimised parameters determined from DFA were confirmed by experimental tests. It is clearly shown mild steel embossed plate (MSEP) shear connector can carry a higher ultimate load with a lower slip can be designed using this approach which results in a greater frictional interlocking with the composite girder, allowing it to sustain a higher transverse load and better bearing capacity while upholding ductility. Thus, implementing the Taguchi approach to perform desirability function analysis appears to be a useful tool for optimising the dimensional parameters of the MSEP shear connector.